Assessing dentinal tubule penetration of an innovative bioactive glass-based root canal sealer through confocal laser scanning microscopy: an in vitro analysis - Barbhai, Sourabh; SR, Srinidhi; Shetty, Rajesh; Joshi, Poonam; Mehta, Vini; Meto, Aida (Giornale Italiano di Endodonzia, 2024)
Aim: To assess and compare the dentinal tubule penetration of zinc oxide eugenol (ZOE)-based, resin-based, bioceramic, and novel bioactive glass-based root canal sealers using a confocal laser scanning microscope (CLSM). Methods: A total of 48 single-rooted permanent teeth were categorized into four groups (n=12) and treated with gutta-percha along with ZOE sealer (Tubli-Seal EWT), resin-based sealer (AH Plus), bioceramic sealer (BioRoot RCS), and bioactive glass (Nishika Canal Sealer-BG). Cross-sections of the roots at 3 mm and 6 mm from the apex were examined under a CLSM to evaluate dentinal tubule penetration. Results: Results indicated that bioceramic sealers exhibited the highest depth of dentinal tubule penetration at both levels, followed by bioactive glass and resin-based sealers. ZOE-based sealer demonstrated the least tubule penetration. Bioactive glass displayed the highest percentage of sealer penetration at 3 mm and 6 mm, with no statistically significant difference observed between bioceramic and bioactive glass groups regarding depth and percentage of dentinal tubule penetration at both levels. Conclusions: Of particular significance is the bioactive glass group, demonstrating the most substantial sealer penetration percentage compared to the other groups at both examined depths.